Role of glycogen availability in sarcoplasmic reticulum Ca2+ kinetics in human skeletal muscle - Ørtenblad, Niels; Nielsen, Joachim; Saltin, Bengt; Holmberg, Hans‐Christer (The Journal of physiology, 2011)
Non‐technical summary Glucose is stored as glycogen in skeletal muscle. The importance of glycogen as a fuel during exercise has been recognized since the 1960s; however, little is known about the precise mechanism that relates skeletal muscle glycogen to muscle fatigue. We show that low muscle glycogen is associated with an impairment of muscle ability to release Ca2+, which is an important signal in the muscle activation. Thus, depletion of glycogen during prolonged, exhausting exercise may contribute to muscle fatigue by causing decreased Ca2+ release inside the muscle. These data provide indications of a signal that links energy utilization, i.e. muscle contraction, with the energy content in the muscle, thereby inhibiting a detrimental depletion of the muscle energy store. Little is known about the precise mechanism that relates skeletal muscle glycogen to muscle fatigue. The aim of the present study was to examine the effect of glycogen on sarcoplasmic reticulum (SR) function in the arm and leg muscles of elite cross‐country skiers (n= 10, 72 ± 2 ml kg−1 min−1) before, immediately after, and 4 h and 22 h after a fatiguing 1 h ski race. During the first 4 h recovery, skiers received either water or carbohydrate (CHO) and thereafter all received CHO‐enriched food. Immediately after the race, arm glycogen was reduced to 31 ± 4% and SR Ca2+ release rate decreased to 85 ± 2% of initial levels. Glycogen noticeably recovered after 4 h recovery with CHO (59 ± 5% initial) and the SR Ca2+ release rate returned to pre‐exercise levels. However, in the absence of CHO during the first 4 h recovery, glycogen and the SR Ca2+ release rate remained unchanged (29 ± 2% and 77 ± 8%, respectively), with both parameters becoming normal after the remaining 18 h recovery with CHO. Leg muscle glycogen decreased to a lesser extent (71 ± 10% initial), with no effects on the SR Ca2+ release rate. Interestingly, transmission electron microscopy (TEM) analysis revealed that the specific pool of intramyofibrillar glycogen, representing 10–15% of total glycogen, was highly significantly correlated with the SR Ca2+ release rate. These observations strongly indicate that low glycogen and especially intramyofibrillar glycogen, as suggested by TEM, modulate the SR Ca2+ release rate in highly trained subjects. Thus, low glycogen during exercise may contribute to fatigue by causing a decreased SR Ca2+ release rate.